Three unrelated chemoreceptors provide Pectobacterium atrosepticum with a broad‐spectrum amino acid sensing capability - Félix Velando; Miguel A. Matilla; Igor B. Zhulin; Tino Krell (Microbial Biotechnology, 2023)
Abstract Amino acids are important nutrients and also serve as signals for diverse signal transduction pathways. Bacteria use chemoreceptors to recognize amino acid attractants and to navigate their gradients. In Escherichia coli two likely paralogous chemoreceptors Tsr and Tar detect 9 amino acids, whereas in Pseudomonas aeruginosa the paralogous chemoreceptors PctA, PctB and PctC detect 18 amino acids. Here, we show that the phytobacterium Pectobacterium atrosepticum uses the three non‐homologous chemoreceptors PacA, PacB and PacC to detect 19 proteinogenic and several non‐proteinogenic amino acids. PacB recognizes 18 proteinogenic amino acids as well as 8 non‐proteinogenic amino acids. PacB has a ligand preference for the three branched chain amino acids L‐leucine, L‐valine and L‐isoleucine. PacA detects L‐proline next to several quaternary amines. The third chemoreceptor, PacC, is an ortholog of E. coli Tsr and the only one of the 36 P. atrosepticum chemoreceptors that is encoded in the cluster of chemosensory pathway genes. Surprisingly, in contrast to Tsr, which primarily senses serine, PacC recognizes aspartate as the major chemoeffector but not serine. Our results demonstrate that bacteria use various strategies to sense a wide range of amino acids and that it takes more than one chemoreceptor to achieve this goal.